Transovarial transmission of mosquito-borne viruses: a systematic review - Janjoter, Sangeeta; Kataria, Divya; Yadav, Mahima; Dahiya, Nisha; Sehrawat, Neelam (Frontiers in Cellular and Infection Microbiology, 2024)
Background: A number of Mosquito borne viruses (MBVs) such as Dengue Virus (DENV), Zika Virus (ZIKV), Chikungunya Virus (CHIKV), West Nile Virus (WNV), Yellow Fever Virus (YFV) poses adverse health impact over the global population. Aedes aegypti and Aedes albopictus are the prime vectors responsible for the transmission of these viruses. The viruses acquire a number of routes for successful transmission including horizontal and vertical transmission. Transovarial transmission is a subset/type of vertical transmission adopted by mosquitoes for transmission of viruses from female to its offspring through eggs/ovaries. It provides a mechanism for these MBVs to persist and maintain their lineage during adverse climatic conditions of extreme hot and cold temperature, dry season or in the absence of susceptible vertebrate host when horizontal transmission is not possible.The publications for this systematic review were searched by using the databases PubMed, Scopus, and Web of Science and websites like World Health Organization (WHO) and the European Centre for Disease prevention and control, using the search terms transovarial transmission, Mosquito borne viruses from 16 May, 2023 to